High-Throughput Screening for Drug Discovery - Saxena, Shailendra K. (IntechOpen, 2022)
The book focuses on various aspects and properties of high-throughput screening (HTS), which is of great importance in the development of novel drugs to treat communicable and non-communicable diseases. Chapters in this volume discuss HTS methodologies, resources, and technologies and highlight the significance of HTS in personalized and precision medicine.